Dietary Protected Sodium Butyrate and/or Olive Leaf and Grape-Based By-Product Supplementation Modifies Productive Performance, Antioxidant Status and Meat Quality in Broilers - Almudena de-Cara; Beatriz Saldaña; Patricia Vázquez; Ana I Rey (MDPI AG, 2023)
To meet the demand for chicken meat production, new additives that promote growth and health without adverse effects on meat quality are being investigated. This study was conducted to investigate the effect of protected sodium butyrate (PSB) (0 vs. 2 g/kg), an olive leaf and grape-based by-product (OLG-mix), or a combined supplementation of PSB and OLG-mix on productive performance, antioxidant status, carcass, and meat quality in broilers. PSB improved performance parameters with greater effect in the initial phase. Both, PSB and OLG-mix increased the plasma superoxide dismutase (SOD); however, PSB supplementation was more effective to delay the lipid oxidation of meat from the initial day of storage. OLG-mix produced meat with greater color intensity, b* value and lesser drip losses than PSB. The combination of PSB + OLG-mix did not produce more marked effects that the individual administration; except to control the oxidation of meat. Linear and positive correlations between antioxidant enzymes and weight gain were observed. Significant linear and negative relationships were quantified between plasma SOD and meat lipid oxidation according to dietary treatment. Therefore, the present study would be a first approximation to the possibilities for predicting growth range and meat quality through the evaluation of the blood oxidative status.